MARKETING RESEARCH AS A TOOL FOR FORMING CLIENT STRATEGY OF COMMERCIAL BANKS (Marketing Journal, 2025)
This article examines the role of marketing research as a key tool in shaping the customer strategy of commercial banks. The necessity of in-depth analysis of customer needs, preferences, and behavior is substantiated as a condition for enhancing competitiveness and sustainability in the banking sector. The paper analyzes the main 259 methods of collecting and processing information used to develop client -focused strategies. Special attention is paid to modern digital tools and Big Data analytics. Practical recommendations are formulated for integrating marketing research results into the strategic management system of commercial banks.
Keywords: marketing research; commercial bank; customer strategy; consumer behavior; segmentation; Big Data; digital analytics